Double Full-Arch Implant-Supported Fixed Complete Dental Prostheses (IFCDPs): advanced monolithic zirconia solutions - Andrea Berzaghi; Sergio Bortolini
Among the latest generation of prosthetic materials, zirconia represents one of the most versatile ceramic materials offering options for rehabilitation of both anterior and posterior sectors. In the last two decades, zirconia frameworks have become increasingly popular in the implant prosthesis and the introduction of CAD/CAM technology has made it possible to approach full-arch restorations in a different way and with promising success rates. In this case report we present Double Full-Arch Implant-Supported Fixed Complete Dental Prostheses (IFCDPs) using digital technology to fabricate advanced monolithic zirconia solutions. We report a brief examination of the advantages of the two solutions in comparison.